Analisis Pemanfaatan Dana Zakat, Infak, Sedekah dan Wakaf dengan Model Fungsi Actuating - Alfadri, Ferri; Harahap, Darwis; Syafitri, Alwijah Indah (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2021)
The management of zakat is carried out with a work and professional system as well as company management and management. However, rules or regulations in accordance with sharia law should not be abandoned. Given the importance of this, this study focuses on the Analysis of Ziswaf Fund Utilization with the Actuating Function Model in the City of Padangsidimpuan. This type of research is qualitative research, the approach used in this research is the management approach. The data collection method uses several instruments, namely: observation, documentation, and interviews. Data analysis used interactive analysis with three steps, namely data reduction, presenting data and drawing conclusions. BAZNAS at Padangsidimpuan city has shown success in managing ZISWAF funds, namely the distribution and distribution of the right and right target, although poverty alleviation has not been implemented significantly, ZISWAF in the city of Padangsidimpuan has helped the beneficiaries' lives through consumptive and productive assistance.Keywords: Actuating, Management, Utilizing, Waqf, Zakat